Enhancing Barn Hygiene through Smart Farming: A Goat Farm Case Study in Besijangkang Using IoT - Nurisma Zenita Dewi; Otniel Andi Hermawan; Abdul Mujiburrohman Luthfi; Saddam Putra Kunsina; Mentari Putri Jati (Universitas Negeri Yogyakarta, 2023)
Besijangkang farms currently rely on conventional management methods, including manual cleaning with broomsticks and inadequate lighting. The scattered droppings and urine on the floor pose challenge for efficient farm maintenance. To address these issues, a solution combining technology and conventional cage management has been proposed to allow remote access for breeders. Researchers have implemented Internet of Things (IoT) utilizing the ESP8266 NodeMCU microcontroller connected to Firebase Web. The integration of IoT in smart farming tools has proven successful and functional. The app enables remote control of the lights through designated buttons. A critical indicator for the goat farm is the urine volume, reaching full capacity at 778 liters, which triggers the illumination of the light near the component box. Furthermore, the DC motor and conveyor effectively manage the dirt load at 09.00, fulfilling their designated functions. By adopting IoT-based smart farming tools, Besijangkang farms can improve their hygiene system, enhance management efficiency, and empower breeders with remote accessibility, revolutionizing traditional farming practices for better productivity and sustainability.